Neuronal correlates of spontaneous fluctuations in fMRI signals in monkey visual cortex: Implications for functional connectivity at rest - Shmuel, Amir (Hum Brain Mapp, 2008)
Recent studies have demonstrated large amplitude spontaneous fluctuations in functional‐MRI (fMRI) signals in humans in the resting state. Importantly, these spontaneous fluctuations in blood‐oxygenation‐level‐dependent (BOLD) signal are often synchronized over distant parts of the brain, a phenomenon termed functional‐connectivity. Functional‐connectivity is widely assumed to reflect interregional coherence of fluctuations in activity of the underlying neuronal networks. Despite the large body of human imaging literature on spontaneous activity and functional‐connectivity in the resting state, the link to underlying neural activity remains tenuous. Through simultaneous fMRI and intracortical neurophysiological recording, we demonstrate correlation between slow fluctuations in BOLD signals and concurrent fluctuations in the underlying locally measured neuronal activity. This correlation varied with time‐lag of BOLD relative to neuronal activity, resembling a traditional hemodynamic response function with peaks at ∼6 s lag of BOLD signal. The correlations were reliably detected when the neuronal signal consisted of either the spiking rate of a small group of neurons, or relative power changes in the multi‐unit activity band, and particularly in the local field potential gamma band. Analysis of correlation between the voxel‐by‐voxel fMRI time‐series and the neuronal activity measured within one cortical site showed patterns of correlation that slowly traversed cortex. BOLD fluctuations in widespread areas in visual cortex of both hemispheres were significantly correlated with neuronal activity from a single recording site in V1. To the extent that our V1 findings can be generalized to other cortical areas, fMRI‐based functional‐connectivity between remote regions in the resting state can be linked to synchronization of slow fluctuations in the underlying neuronal signals. Hum Brain Mapp 2008. © 2008 Wiley‐Liss, Inc.